Investigation of the functional pathogenesis of mild cognitive impairment by localisation‐based locus coeruleus resting‐state fMRI. Issue 18 (11th August 2022) - Liebe, Thomas; Dordevic, Milos; Kaufmann, Jörn; Avetisyan, Araks; Skalej, Martin; Müller, Notger
Abstract: Dementia as one of the most prevalent diseases urges for a better understanding of the central mechanisms responsible for clinical symptoms, and necessitates improvement of actual diagnostic capabilities. The brainstem nucleus locus coeruleus (LC) is a promising target for early diagnosis because of its early structural alterations and its relationship to the functional disturbances in the patients. In this study, we applied our improved method of localisation‐based LC resting‐state fMRI to investigate the differences in central sensory signal processing when comparing functional connectivity (fc) of a patient group with mild cognitive impairment (MCI, n = 28) and an age‐matched healthy control group ( n = 29). MCI and control participants could be differentiated in their Mini‐Mental‐State‐Examination (MMSE) scores ( p < .001) and LC intensity ratio ( p = .010). In the fMRI, LC fc to anterior cingulate cortex (FDR p < .001) and left anterior insula (FDR p = .012) was elevated, and LC fc to right temporoparietal junction (rTPJ, FDR p = .012) and posterior cingulate cortex (PCC, FDR p = .021) was decreased in the patient group. Importantly, LC to rTPJ connectivity was also positively correlated to MMSE scores in MCI patients ( p = .017). Furthermore, we found a hyperactivation of the left‐insula salience network in the MCI patients. Our results and our proposed disease model shed new light on the functional pathogenesis of MCI by directing to attentional network disturbances, which could aid new therapeutic strategies and provide a marker for diagnosis and prediction of disease progression. Abstract : The growing prevalence of dementia urges for a better understanding of the underlying mechanisms and improvement of diagnostic capabilities. Localisation‐based locus coeruleus (LC) resting‐state functional magnetic resonance imaging reveals how LC functional connectivity to anterior and posterior cingulate cortex, left anterior insula and to the right temporoparietal junction plays a prominent role in the functional pathogenesis of mild cognitive impairment. LC to right temporoparietal junction connectivity could provide a marker for disease monitoring.